Structural Study Of Epoxidized Natural Rubber (Enr-50) And Its Derivatives Synthesized Via Epoxide Ring-Opening Reactions Using Nmr Techniques - Hamzah, Rosniza (2015)
Satu terbitan siklik ditiokarbonat yang terdiri daripada getah asli terepoksida (ENR-50) dan tiga jenis hibrid ENR-50/titania (TiO2), ENR-50/zirkonia (ZrO2) dan kompleks ENR-50/stanum (Sn) telah disediakan. Teknik FTIR, 1D NMR; 1H-, 13C-, 119Sn-NMR, 2D NMR; HMQC, HMBC, COSY, TGA, DSC, TEM, SEM-EDX dan XRD telah digunakan untuk mencirikan terbitan dan hibrid ENR. Suatu susunan triad ENR-50 berjaya ditandakan menggunakan teknik NMR dan gabungan terbitan siklik ditiokarbonat ENR-50. Suatu terbitan siklik ditiokarbonat ENR-50 telah disintesis daripada tindak balas ENR-50 dan karbon disulfide (CS2) dengan kehadiran mangkin 4-dimetilaminopridina (DMAP) pada suhu refluks (47 °C) selama 3 jam. Kedua-dua hibrid ENR/TiO2 dan ENR/ZrO2 telah disediakan daripada tindak balas pembukaan gelang epoksida ENR-50 pada keadaan berasid lembut (ENR-50 terawat asid) dan berbes (ENR-50 terawat bes) yang seterusnya ditindak balaskan dengan pemula masing-masing melalui teknik sol-gel pada suhu refluks (60 °C) selama 24 jam. Sumber pemula TiO2 dan ZrO2 masing-masing adalah Ti(OCH2CH2CH3)4 dan Zr(OCH2CH2CH3)4. A cyclic dithiocarbonate derivatives of epoxidized natural rubber (ENR-50) and three types of hybrids comprising ENR-50/titania (TiO2), ENR-50/zirconia (ZrO2) and ENR-50/tin (Sn) complex were prepared. FTIR, 1D NMR; 1H-, 13C-, 119Sn-NMR, 2D NMR; HMQC, HMBC, COSY, TGA, DSC, TEM, SEM-EDX and XRD techniques were used to characterize the ENR derivative and hybrids. A triad sequence of ENR-50 was successfully assigned using NMR techniques consolidated by the cyclic dithiocarbonate derivative of ENR-50. A cyclic dithiocarbonate derivative of ENR-50 was synthesized from the reaction of purified ENR-50 with carbon disulfide (CS2), in the presence of 4-dimethylaminopyridine (DMAP) as catalyst at reflux temperature (47 °C) for 3 hours. Both ENR/TiO2 and ENR/ZrO2 hybrids were prepared from epoxide ring opening reaction of ENR-50 at mild acidic (acid treated ENR-50) and basic (base treated ENR-50) conditions which later reacted with the respective precursors via sol-gel technique at reflux temperature (60 °C) for 24 hours. The respective source of TiO2 and ZrO2 precursors used were Ti(OCH2CH2CH3)4 and Zr(OCH2CH2CH3)4.